2021
DOI: 10.1007/s10593-021-02914-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of biologically active derivatives of 2-aminobenzothiazole

Abstract: The minireview considers the current trends in the synthesis of some biologically active compounds based on 2-aminobenzothiazole. The presented information covers publications of the last five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…Bu protonların Hz değerlerinin 12 çıkması olması yapının trans pozisyonda olduğunu göstermektedir [38]. Spekturumda 7,34 ppm ve 7,60 ppm arasında gözlenen 7H'lık iki doublet ( 3 J H8H9/H10-H9/H8/H10 = 12,00 Hz) ve üç singlet pikler tuzun Habt + 'nin amino grubu protonları (H 18 6,79 ppm (1H, d) [ 3 J H18-H19 = 7,60 Hz] C 9 139,66 ppm H 19 7,74 ppm (1H, d) [ 3 J H19-H18 = 5,20 Hz] C 10 131,14 ppm H 24 7,40 ppm (2H, s) C 11 , C 16 153,97 ppm H 26 3,98 ppm (2H, q) [ 3 J H26-H27 = 6,80 Hz] C 12 114,12 ppm H 27 1,31 ppm (3H, t) [ 3 J H27-H26 = 6,80 Hz] C 18 121,18 ppm C 19 117,01 ppm C 20 163,93 ppm C 21 106,69 ppm C 22 132,23 ppm C 23 145,27 ppm C 26 63,76 ppm C 27 15,40 ppm…”
Section: 1 6 Tuzunun Nmr Sonuçlarıunclassified
See 1 more Smart Citation
“…Bu protonların Hz değerlerinin 12 çıkması olması yapının trans pozisyonda olduğunu göstermektedir [38]. Spekturumda 7,34 ppm ve 7,60 ppm arasında gözlenen 7H'lık iki doublet ( 3 J H8H9/H10-H9/H8/H10 = 12,00 Hz) ve üç singlet pikler tuzun Habt + 'nin amino grubu protonları (H 18 6,79 ppm (1H, d) [ 3 J H18-H19 = 7,60 Hz] C 9 139,66 ppm H 19 7,74 ppm (1H, d) [ 3 J H19-H18 = 5,20 Hz] C 10 131,14 ppm H 24 7,40 ppm (2H, s) C 11 , C 16 153,97 ppm H 26 3,98 ppm (2H, q) [ 3 J H26-H27 = 6,80 Hz] C 12 114,12 ppm H 27 1,31 ppm (3H, t) [ 3 J H27-H26 = 6,80 Hz] C 18 121,18 ppm C 19 117,01 ppm C 20 163,93 ppm C 21 106,69 ppm C 22 132,23 ppm C 23 145,27 ppm C 26 63,76 ppm C 27 15,40 ppm…”
Section: 1 6 Tuzunun Nmr Sonuçlarıunclassified
“…Çalışmanın diğer bazik bileşeni olan 2-aminobenzotiyazol türevlerin, antiviral, ayrıca antimikrobiyal, antiinflamatuar, antidiyabetik, analjezik, antioksidan, antidepresan, antikonvülsan, antianjinal, antitümör, antelmintik, antimalaryal, fungisidal, insektisidal ve herbisidal etkileri vardır [18][19][20][21][22][23]. 2-Aminobenzotiyazol türevlerinin organik türevleri daha fazla çalışılmış olsa da proton transfer tuzu ve metal kompleksleri çok azdır.…”
Section: Introductionunclassified
“…5,6 Benzothiazoles and their analogues are important building blocks and synthetic intermediates in the synthesis of new drugs, pesticides, and dyes, and are utilized in medicinal chemistry. 7,8 Derivatives of benzothiazole have been reported to show a wide spectrum of pharmacological activities and agrochemical applications like anti-convulsant, 9 antiallergy, 10 antifungal, 10 anti-microbial, 11 anti-oxidant, 12 anti-inflammatory, 12 anti-diabetic, 13 neuroprotective, and many others 14 (Figure 1). On the other hand, benzothiazoles are also widely used in a variety of consumer and industrial products such as nonlinear optics (NLOs), organic light-emitting diodes (OLEDs), fluorescent probes, luminescence, chemosensors, 1517 and liquid crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, aminobenzothiazole has gained significant attention due to its pharmacological activity, including anti‐inflammatory, antifungal, anticonvulsant, analgesics, and anticancer activity. [ 4–9 ] It is reported that nitrogen‐containing heterocyclic rings like aminobenzothiazole offer a polarized character, which plays a significant role in the stability of the molecule‐receptor complex. It generally increases the complex stability by establishing an optimum interaction that produces anticancer effects.…”
Section: Introductionmentioning
confidence: 99%